THE USE OF MEDIA FOR SCIENCE TEACHING IN ISLAMIC SCHOOLS - Abd Ghofur (IKIP PGRI Bojonegoro, 2018)
Abstract: This paper aims to describe the use of media in science learning in terms of three indicators, namely: a) diffusion of innovation, b) implementation and institutionalization, and c) policies and regulations. This research was conducted for four months using qualitative descriptive design with data collection technique through questionnaire, interview, and observation. The subjects of the study were class VII on MTs Putra Putri Lamongan and MTs Maslakul Huda Paciran selected by purposive sampling. The results showed that science teachers in Islamic schools utilize various media of learning in the form of visual and audiovisual media designed as a medium of teaching science, for example LCD projector, props, etc. In addition, teachers also develop their own simple media designed to be utilized in science teaching, such as cloth, water, soil, and so forth. Technically, teachers are documenting the use of instructional media in the Lesson Plans (RPP) which refer to the 2013- curriculum format , but the RPP is not always brought during the learning process. In addition, school policy does not provide written regulations for teachers to use the media in the learning process.Â Keywords: the use of media, science teachingÂ Abstrak: Tulisan ini bertujuan untuk mendeskripsikan pemanfaatan media dalam pembelajaran sains yang ditinjau dari tiga indikator, yakni a) difusi inovasi, b) implementasi dan pelembagaan, serta c) kebijakan dan regulasi. Penelitian ini dilakukan selama empat bulan menggunakan rancangan deskriptif kualitatif dengan teknik pengumpulan data melalui angket, wawancara, dan observasi. Subyek penelitian adalah kelas VII pada MTs Putra Putri Lamongan dan MTs Maslakul Huda Paciran yang dipilih secara purposive sampling. Hasil penelitian menunjukkan bahwa guru sains di sekolah Islam memanfaatkan ragam media pembelajaran dalam bentuk media visual dan audio visual yang didesain sebagai media pembelajaran sains, misal LCD proyektor, alat peraga, dll. Selain itu, guru juga mengembangkan media sederhana sendiri yang didesain untuk dimanfaatkan dalam pembelajaran sains, misalnya kain, air, tanah, dan lain sebagainya. Secara teknis, guru mendokumentasikan pemanfaatan media pembelajaran tersebut dalam Rencana Pelaksanaan Pembelajaran (RPP) yang mengacu format Kurikulum 2013, namun RPP tersebut tidak selalu dibawa saat proses pembelajaran. Selain itu, kebijakan sekolah tidak memberikan regulasi secara tertulis untuk guru melakukan pemanfaatan media dalam proses pembelajaran. Â Kata Kunci: pemanfaatan media, pembelajaran sains